2015
DOI: 10.1103/physrevb.92.214116
|View full text |Cite
|
Sign up to set email alerts
|

Proton configurations in the hydrogen bonds ofKH2PO4as seen by resonant x-ray diffraction

Abstract: KH2PO4 (KDP) belongs to the class of hydrogen-bonded ferroelectrics, whose paraelectric to ferroelectric phase transition is driven by the ordering of the protons in the hydrogen bonds. We demonstrate that forbidden reflections of KDP, when measured at an x-ray absorption edge, are highly sensitive to the asymmetry of proton configurations. The change of average symmetry caused by the 'freezing' of the protons during the phase transition is clearly evidenced. In the paraelectric phase, we identify in the reson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Interestingly, forbidden reflections that originate from interference between different scattering channels (e.g. E1.E1 with E1.E2) have been experimentally observed (Kirfel et al, 2002;Collins et al, 2003;Beutier et al, 2014Beutier et al, , 2015Richter et al, 2014;Kokubun et al, 2001;Oreshko et al, 2012). However, local chirality could not be fully investigated in these experiments since linearly polarized X-rays were used.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, forbidden reflections that originate from interference between different scattering channels (e.g. E1.E1 with E1.E2) have been experimentally observed (Kirfel et al, 2002;Collins et al, 2003;Beutier et al, 2014Beutier et al, , 2015Richter et al, 2014;Kokubun et al, 2001;Oreshko et al, 2012). However, local chirality could not be fully investigated in these experiments since linearly polarized X-rays were used.…”
Section: Introductionmentioning
confidence: 98%
“…In the low- T FE phase, the protons are off-center ordered in the HBs, which are nearly perpendicular to the FE c -axis. 4 KDP becomes paraelectric (PE) at higher temperatures. 5 , 6 The proton off-centering stretches the O–O distance and thus correlates to the lattice expansion and heavy-ion distortions.…”
Section: Introductionmentioning
confidence: 99%
“…The prototype material is potassium dihydrogen phosphate (KDP) discovered in 1935, where strong hydrogen bonds (HBs) link the tetrahedral PO 4 units. In the low- T FE phase, the protons are off-center ordered in the HBs, which are nearly perpendicular to the FE c -axis . KDP becomes paraelectric (PE) at higher temperatures. , The proton off-centering stretches the O–O distance and thus correlates to the lattice expansion and heavy-ion distortions.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the DAFS method [5,6], where the spectra of allowed Bragg reflections are studied, in the forbidden Bragg reflections any contribution from non-resonant Thomson scattering is absent making subtle resonant scattering more pronounced. In numerous studies of forbidden reflections, the great possibilities of the method were demonstrated using examples of determining the magnetic structure [7][8][9], orbital and charge ordering [10,11], local chirality [12,13] and thermal displacements of atoms [14][15][16][17] etc. Particularly exciting is the opportunity to study variations of local properties when the crystal is exposed to external influences.…”
Section: Introductionmentioning
confidence: 99%